Pemberdayaan UMKM Menuju Rintisan Desa Devisa di Desa Tropodo Kabupaten Sidoarjo - Sediono Sediono; M. Fariz Fadillah Mardianto; Sa’idah Zahrotul Jannah; Marcel Laverda Subiyanto; Antonio Nikolas Manuel Bonar Simamora; Citra Imama; Arum Eka Ismiranda Putri (LPPM Universitas Trunojoyo Madura, 2022)
MSMEs play an important role in Indonesia's economic stability, which is in line with the 8th point of the Sustainable Development Goals, namely Decent Work and Economic Growth. Such as MSMEs in Tropodo village with their superior product, namely Kembang Telang which is moving to try to become a “Desa Devisa” in order to be able to bring local products to foreign countries. The implementation method used in order to realize Tropodo Village into a “Desa Devisa” through several stages, namely: identification of activities, socialization of activities, identification of village potential, formation of MSME cadres to mobilize micro business actors, marketing research with a statistical approach to determine the potential and target market, presentation of research results, training and mentoring activities with students, innovation and implementation of training activities by inviting resource persons who are experts in their fields, monitoring and evaluating the implementation of activities, publication of activities, project sustainability plan. The result of community service is that MSMEs get useful knowledge and can continue to be developed, especially to improve the community's economy through marketing MSME digital products both domestically and globally.